Esporulação de Botryotinia ricini em diferentes meios de cultura - Chagas, Haroldo Antunes [UNESP]; Rosa, Daniel Dias [UNESP]; Basseto, Marco Antonio [UNESP]; Zanotto, Maurício Dutra [UNESP]; Furtado, Edson Luiz [UNESP] (Universidade Federal de Uberlândia (UFU), 2009)
The castor bean plant is a tropical species and is subject to various diseases, which cause great losses. Among these diseases, the gray mold (Botryotinia ricini) is one of the most important. The fungus spore production was evaluated in the media of cultures BDA; Oats-Agar; Mazeina-Agar; Rice-Agar; castor-bean crushed leaves-agar (FM), FM-CaCO3; V8 juice to 5% (V8-5%); V8-10%; V8-20% and tomato juice at 5% (TJ-5%); TJ-10% and TJ-20%. The production of spore in different media of cultures was evaluated at 8(th) days of incubation. The data were analyzed using the comparison of means, through the test Tukey a 5% probability, and the data processed for (X + 1) (0.5). All means of crops tested were able to produce conidia, but the best results was obtained with the culture medium V8-20% (5.7 x 10(6) conidia/mL) and BDA (3.5 x 10(6) conidia/mL).

A mamoneira é uma espécie tropical e está sujeita a diversas doenças, que causam grandes prejuízos, dentre essas, o mofo cinzento (Botryotinia ricini) é uma das mais importantes. A esporulação deste fungo foi avaliada nos meios de culturas BDA; Aveia-agar; Mazeina-agar; Arroz-agar; Folhas de mamona triturada-ágar (FM); FM-CaCO3; suco V8 a 5% (V8-5%); V8-10%; V8-20%; suco de tomate a 5% (TJ-5%); TJ-10%; TJ-20%. A esporulação do fungo, nos diferentes meios de culturas, foi avaliada no 8˚ dia de incubação. Os dados foram analisados utilizando método de comparação entre médias, através do teste Tukey a 5% de probabilidade, sendo os dados transformados para (X+1)0,5. Todos os meios de culturas testados se mostraram aptos para a produção de conídios, mas obteve-se os melhores resultados no meio de cultura V8-20%, com 5,7 x 106 conídios/mL, ficando em segundo lugar o meio BDA, com uma esporulação média de 3,5 x106 conídios/mL.
Sporulation of Botryotinia ricini in different culture media
Keywords: Amphobotrys ricini; Ricinus communis; Inoculum; Genetic selection